2010
DOI: 10.1103/physreva.82.010701
|View full text |Cite
|
Sign up to set email alerts
|

Absolute cross sections for dissociative electron attachment to HCN and DCN

Abstract: Absolute partial cross sections for the formation of CN − in dissociative electron attachment to HCN and DCN have been measured using a time-of-flight ion spectrometer combined with a trochoidal electron monochromator to be 940 pm 2 for CN − /HCN and 340 pm 2 for CN − /DCN at peaks of the bands due to the 2 -shape resonance. The dissociative electron attachment bands were then recorded under higher resolution, 60 meV, with a trochoidal monochromator plus quadrupole mass filter combination and found to have a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 25 publications
(53 reference statements)
5
21
0
Order By: Relevance
“…7, respectively, for HCN and DCN. In these figures, further compare the present results to the experimental values of May et al [1].…”
Section: Dea Cross Sectionsupporting
confidence: 76%
See 1 more Smart Citation
“…7, respectively, for HCN and DCN. In these figures, further compare the present results to the experimental values of May et al [1].…”
Section: Dea Cross Sectionsupporting
confidence: 76%
“…Recently, May et al conducted a time-of-flight ion spectrometry experiment to measure the isotope effect in dissociative electron attachment (DEA) to HCN [1]. The authors measured a σ (CN − /HCN) /σ (CN − /DCN) ratio of 2.76 at 333 K below 3 eV in electron energy.…”
Section: Introductionmentioning
confidence: 99%
“…Burrow et al 5 reported electron transmission spectra and identified a low-lying shape resonance. More recently, May et al 6 reported absolute partial cross sections for the formation of CN − using a timeof-flight ion spectrometer. Calculations were also performed a while ago by Jain and Norcross 7 using a model potential method and by Varambhia and Tennyson who applied the R-matrix technique.…”
Section: Introductionmentioning
confidence: 99%
“…An ab initio calculation of DEA to HCN [33,34] (validated experimentally [35]) led to the surprising finding that although the electronic structure is the same as in the case of acetylene, and also the potential surfaces of the two anions are similar (i.e., an energy barrier is encountered for dissociation in linear geometry but may be by-passed by bending the à anion out of linearity), a dynamics calculation revealed that the hydrogen prefers to tunnel through the barrier rather than traveling around it in HCN. This could also happen for the O-H hydrogen in formic acid; the dissociation of the à resonance would then proceed without involvement of the C-H hydrogen and would also explain the present experimental finding.…”
mentioning
confidence: 99%